2021
DOI: 10.1093/qjmed/hcab202
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin D levels and prognosis in a COVID-19 pediatric population: a systematic review

Abstract: Aim We aim to study the relationship between vitamin D level, risk and severity of COVID-19 infection in pediatric population through systematic review. Methods We searched PubMed, CINAHL, EMBASE, Cochrane Library and Google Scholar from December 2019 to June 2021 for retrieving articles studying association between vitamin D deficiency with COVID-19. Qualitative details were synthesized in evidence table and quantitative dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“… 38 Improvement in the severity of COVID‐19 through supplementation with vitamin D was also stated. 38 Nearly half of the pediatric COVID‐19 patients had vitamin D deficiency. 38 These findings were similar to the results of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 38 Improvement in the severity of COVID‐19 through supplementation with vitamin D was also stated. 38 Nearly half of the pediatric COVID‐19 patients had vitamin D deficiency. 38 These findings were similar to the results of the current study.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Nearly half of the pediatric COVID‐19 patients had vitamin D deficiency. 38 These findings were similar to the results of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these results derive from the analysis of only 102 cases, so larger studies are needed. The absent definition of the serum 25(OH)D cutoff level used to identify vitamin D deficiency is another limitation of this systematic review [ 172 ]. Previously, we discussed that breastfeeding may contribute to decrease the risk of contract COVID-19 in infancy.…”
Section: Vitamin D Supplementation In Childhoodmentioning
confidence: 99%
“…Given the appearance of 8 new variants whose virulence and coverage by current vaccines are still under study [2,3], it is important to study modifiable risk factors that may reduce the risk of developing severe or fatal forms of SARS-CoV-2 infection. One of the most studied modifiable risk factors has been vitamin D. So far, several systematic and meta-analytic studies have been published, which have concluded that there may be a cause-effect relationship between low serum 25-hydroxyvitamin D (25(OH)D3) and increased mortality and severity due to SARS-CoV-2 infection [4][5][6][7][8][9]. However, the robustness of this causeand-effect relationship is currently being questioned and it has been suggested that this premature conclusion should be taken with caution for several rea-sons [10].…”
Section: Introductionmentioning
confidence: 99%